MERUNUT EMPIRISME, ISLAM DAN MODERNITAS DALAM RELEVANSINYA PADA MASA KEKINIAN - Muhammad Labib Syauqi (Faculty of Ushuluddin UIN Syarif Hidayatullah Jakarta, 2023)
The Philosophy of Empiricism is a branch of Epistemology whose existence is increasingly being ignored. Even though empiricism has had strong roots since its emergence. Empiricism is also closely related to the culture of inductive thinking in Islam. Empiricism with the theory of Tabula rasa also makes an important contribution to the world of education. Empiricism also has a powerful effect on the development of science, technology and the industrial revolution. Although empiricism as a method of philosophy is not absolutely true, at a certain level, empiricism has significance. This article uses the library research method by operationalizing Kuntowijoyo's theory of the history of thought to capture the development of thought more comprehensively. This study concludes that empiricism is closely related to Islam and modern reasoning, which is all based on empirical things. This standard of empiricism then greatly influences the values used in modern reasoning.